Evaluation of Serum Levels of Cytokines in Acute Apical Abscess: A Longitudinal Observational Study - Palafox-Sánchez, Claudia Azucena; Cruz, Alvaro; Salazar-Camarena, Diana Celeste; Gascón, Luis Gerardo; Cintra, Luciano Tavares Angelo [UNESP]; Muñoz-Valle, José Francisco; García-Arellano, Samuel; Estrela, Carlos; Menchaca-Tapia, Paula Annahi (Elsevier, 2023)
Introduction: Cytokine levels are related to the aethiopathogenia of acute apical abscesses (AAA); however, the specific cytokine profiles in these cases are unclear. This study aimed to investigate the changes in systemic cytokine levels in patients with AAA and trismus onset, postantibiotic treatment, and postroot canal disinfection. Methods: In total, 46 AAA patients with trismus and 32 control subjects were included. After seven days of antibiotic therapy, root canal disinfection was performed in the AAA patients. The serum levels of cytokines were evaluated at basal, seven, and 14 days after endodontic treatment. Quantification of cytokines from T helper (Th) 1, Th2, Th17, and regulatory T cells profiles was determined using the BioPlex MagPix system, and the obtained data were analyzed using SPSS statistical software (P < .05). Results: AAA patients showed higher tumor necrosis factor-alpha (TNF-α), interleukin (IL) -6, and IL-10 levels than control subjects, at basal measurement (P < .05); there were similar levels of interferon gamma, IL-1β, IL-4, and IL-17 between groups (P > .05). IL-6 and IL-10 levels decreased after antibiotic treatment (P < .05), which was also associated with clinical improvement in patients with AAA and trismus. Patients with AAA had a positive correlation with higher serum levels of IL-6 and IL-10. In addition, TNF-α levels decreased only after antibiotic and endodontic treatment. Conclusions: In conclusion, patients with AAA had increased systemic serum levels of TNF-α, IL-6, and IL-10. Moreover, increased levels of IL-6 and IL-10 are associated with acute inflammatory symptoms. However, IL-6 and IL-10 levels decreased after antibiotic treatment, while TNF-α levels decreased after antibiotic and endodontic treatment.
Keywords: Acute apical abscess; apical periodontitis; odontogenic infections; serum cytokine levels